2008
DOI: 10.1103/physrevlett.100.066603
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nonadiabaticity and Damping in Permalloy Studied by Current Induced Spin Structure Transformations

Abstract: By direct imaging we determine spin structure changes in Permalloy wires and disks due to spin transfer torque as well as the critical current densities for different domain wall types. Periodic domain wall transformations from transverse to vortex walls and vice versa are observed, and the transformation mechanism occurs by vortex core displacement perpendicular to the wire. The results imply that the nonadiabaticity parameter does not equal the damping , in agreement with recent theoretical predictions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
6
56
0
2
Order By: Relevance
“…We group the DWs by their topology, as determined from the PEEM imaging. The threshold current densities for transverse walls are larger compared to those for vortex walls in agreement with previous reported work [17]. For vortex domain walls the threshold current density decreases as the arm width is increased for both Py 99 Gd 1 and Py 90 Gd 10 .…”
supporting
confidence: 80%
See 1 more Smart Citation
“…We group the DWs by their topology, as determined from the PEEM imaging. The threshold current densities for transverse walls are larger compared to those for vortex walls in agreement with previous reported work [17]. For vortex domain walls the threshold current density decreases as the arm width is increased for both Py 99 Gd 1 and Py 90 Gd 10 .…”
supporting
confidence: 80%
“…For transverse domain walls the threshold current is set by the hard axis in-plane anisotropy with the edge roughness contributing a further increase of the threshold current due to extra pinning [17]. is the Gilbert damping and is the non-adiabaticity parameter, as the vortex domain wall is displaced the vortex core attains a transverse displacement dependent on its polarity.…”
mentioning
confidence: 99%
“…The depinning mechanism can reveal details of the interaction between the spin-polarized current and the magnetization, as it was predicted to be often accompanied by a spin structure transformation [3]. Furthermore, other key parameters such as the critical current density [4,5,6,7], the DW velocity [8,9,10], and transformation of the DW's structure [9,10] contain information on the relation between the non-adiabaticity and the damping [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth comparing our result to available experimental ones. Thomas et al [94], Heyne et al [109], and Eltschka et al [111] have found that vortex cores exhibit a much larger nonadiabaticity (…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the nonadiabaticity for current-induced domain wall motion, has led to a number of theoretical [23][24][25][98][99][100][101][102][103][104][105][106] and experimental studies [94,[107][108][109][110][111][112] to determine the nonadiabatic spin torque parameter. Several mechanisms for the nonadiabatic spin transfer torque have been proposed.…”
Section: Non-local Spin Transfer Torque For a Narrow Domain Wallmentioning
confidence: 99%